2014
DOI: 10.1038/nbt.2938
|View full text |Cite|
|
Sign up to set email alerts
|

Linking T-cell receptor sequence to functional phenotype at the single-cell level

Abstract: Although each T lymphocyte expresses a T-cell receptor (TCR) that recognizes cognate antigen and controls T-cell activation, different T cells bearing the same TCR can be functionally distinct. Each TCR is a heterodimer, and both α- and β-chains contribute to determining TCR antigen specificity. Here we present a methodology enabling integration of information about TCR specificity with information about T cell function. This method involves sequencing of TCRα and TCRβ genes, and amplifying functional genes ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
572
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(596 citation statements)
references
References 45 publications
21
572
3
Order By: Relevance
“…Compared with other strategies that aim to validate functional TCRs from single T cells (15,16), our approach includes the directed cloning of amplified variable regions into IVT vectors providing the TCR-a/b constant regions for extremely rapid generation of full-length TCRs for validation assays that include the determination of epitope specificity for any antigen. Although next-generation sequencing-based methods and the use of barcodes allows for identification of potentially hundreds of a/b-TCRs in a single experiment (22), validation of these TCRs still requires subsequent cost-intensive gene synthesis and cloning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other strategies that aim to validate functional TCRs from single T cells (15,16), our approach includes the directed cloning of amplified variable regions into IVT vectors providing the TCR-a/b constant regions for extremely rapid generation of full-length TCRs for validation assays that include the determination of epitope specificity for any antigen. Although next-generation sequencing-based methods and the use of barcodes allows for identification of potentially hundreds of a/b-TCRs in a single experiment (22), validation of these TCRs still requires subsequent cost-intensive gene synthesis and cloning.…”
Section: Discussionmentioning
confidence: 99%
“…Turchaninova and colleagues (21) introduced an interesting cell-based emulsion real-time PCR (RT-PCR) technique for the identification of TCR-a/b chain pairing. Most recently, Han and colleagues (22) reported an elegant TCR profiling and phenotyping approach using the MiSeq platform. In parallel, many immunomics tools have evolved, including immunoinformatics enabling in silico prediction of epitopes for whole proteomes following in vitro validation of peptide candidates by HLA binding and cellular immune assays (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the combination of pheno typic analyses and sequencing of T cell receptors (TCRs), which act as unique barcodes for each T cell, has made it possible to investigate the phenotype of clonal descendants of single cells. This has uncovered a great degree of heterogeneity in the type of T cell response generated from single T cells, regardless of the initial stimulus 30,31 , and may indicate that generating many functionalities associated with different T cell subsets from individual T cells is advantageous for host immunity. Taking this further, single-cell RNA sequen cing has revealed that there is a great deal of hetero geneity among individual cells in populations of what are perceived to be homogeneous T helper cell subsets, as it was recently shown with single T H 17 cells that exhibited a range of phenotypes from pathogenic to regulatory in nature 32,33 .…”
mentioning
confidence: 99%
“…A recently published work51 has finally coupled the analysis of α ‐chain and β ‐chain sequences with the expression of a panel of genes characteristic of differentiated T cells. This analysis showed how T cells bearing the same TCR‐ α and TCR‐ β sequences can exhibit substantial differences in the expression of cytokines and transcription factors, demonstrating for the first time that T cells derived from the same progenitor can actually differentiate towards different mature T cells.…”
Section: Heterogeneity In the Immune Systemmentioning
confidence: 99%